Physical Activity and Postpartum Quality of Life: A Cross-Sectional Analysis - Qur`ana Fauziyah; Faizah Betty Rahayuningsih (Poltekkes Kemenkes Tanjung Karang, 2026)
The postpartum period is a critical phase marked by substantial physical and psychological changes that may affect maternal well-being and quality of life. Physical activity plays an important role in supporting recovery and facilitating adaptation to new maternal roles. This study aimed to analyze the relationship between physical activity capacity and quality of life among postpartum mothers in the working areas of the Tlogowungu and Miri Community Health Centers. A quantitative cross-sectional design was applied. The study involved 90 postpartum mothers selected using purposive sampling. Physical activity capacity was measured using a postpartum physical activity questionnaire based on activities of daily living, while quality of life was assessed using the Indonesian version of the Maternal Postpartum Quality of Life Instrument (MPQOL-I). Data were analyzed using the Chi-square test with a significance level of p < 0.05. The results showed that most respondents were classified as independent in physical activity (73.3%) and had a high quality of life (86.7%). Chi-square analysis demonstrated a significant relationship between physical activity capacity and quality of life in both the Tlogowungu group (p = 0.006) and the Miri group (p = 0.001). Independent t-test results indicated significant differences in mean physical activity capacity and quality of life between the two study areas (p = 0.034). Physical activity capacity is significantly associated with quality of life among postpartum mothers. These findings highlight the importance of integrating safe and appropriate physical activity promotion into postpartum care services in primary health care settings to improve maternal well-being.